Diagnosis of Henoch-Schonlein purpura in a child presenting withbilateral acute scrotum - Palumbo, E. (Acta Biomedica Atenei Parmensis, 2009)
Schonlein-Henoch syndrome (HSP) is one of the manifestations of acute systemic vasculitis related to circulating immune complexes including IgA. It usually involves the kidney, gastrointestinal tract, joints and skin. Except for rare cases that progress to renal failure, it is a disease which heals without complications. The first case of male genital involvement in this syndrome was reported by Allen et al in 1960. Since then, several reports of this condition with an incidence of scrotal involvement varying from 2 to 38% have been described. The involvement of the male genitalia presenting as the only initial manifestation of SHS is so unusual that the diagnosis can easily be missed. In literature rare cases have been reported in which acute scrotum was the initial presenting symptom in patients affected by HSP. We report a case of HSP presenting as acute scrotum in a 5-year-old boy hospitalized for fever and viral bronchopneumonia.